Wurlitzer of Cincinnati the name that means music to millions - Palkovic, Mark (History Press, 2015)
"Established in Cincinnati in 1856 by German immigrant Franz Rudolph Wurlitzer, the music dealer became the largest outlet for band instruments in the United States by 1865. During the silent film era in the early twentieth century, Wurlitzer manufactured nearly 2,250 theater organs, affectionately dubbed Mighty Wurlitzers. Many of these instruments still provide concert music today. During the Big Band era of the 1930s to 1950s, the company's colorful coin-operated jukeboxes were such popular fixtures in bars and dance halls that the U.S. Postal Service honored them with a commemorative stamp. Although the company was sold in 1988, the Wurlitzer name continues to be held in high esteem by the city of Cincinnati." (Provided by publisher)